Culture of Safety: Impact on Improvement in Infection Prevention Process and Outcomes - Braun, Barbara I. (Curr Infect Dis Rep, 2020)
PURPOSE: Safety culture is known to be related to a wide range of outcomes, and measurement of safety culture is now required for many hospitals in the U.S.A. In previous reviews, the association with outcomes has been limited by the research design and strength of the evidence. The goal of this review was to examine recent literature on the relationship between safety culture and infection prevention and control-related (IPC) processes and healthcare-associated infections (HAIs) in U.S. healthcare organizations. We also sought to quantitatively characterize the challenges to empirically establishing these relationships and limitations of current research. RECENT FINDINGS: A PubMed search for U.S. articles published 2009–2019 on the topics of infection prevention, HAIs, and safety culture yielded 448 abstracts. After screening, 55 articles were abstracted for information on purpose, measurement, analysis, and conclusions drawn about the role of safety culture in the outcome. Approximately ½ were quality improvement (QI) initiatives and ½ were research studies. Overall, 51 (92.7%) concluded there was an association between safety culture and IPC processes or HAIs. However, only 39 studies measured safety culture and 26 statistically analyzed safety culture data for associations. Though fewer QI initiatives analyzed associations, a higher proportion concluded an association exists than among research studies. SUMMARY: Despite limited empirical evidence and methodologic challenges to establishing associations, most articles supported a positive relationship between safety culture, improvement in IPC processes, and decreases in HAIs. Authors frequently reported experiencing improvements in safety culture when not directly measured. The findings suggest that associations between improvement and safety culture may be bi-directional such that positive safety culture contributes to successful interventions and implementing effective interventions drives improvements in culture. Greater attention to article purpose, design, and analysis is needed to confirm these presumptive relationships.